1997
DOI: 10.1007/s11664-997-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of metal-semiconductor-metal GaN photoconductors

Abstract: Metal-semiconductor-metal photoconductors made on GaN usually exhibit a slow response time and a low responsivity. We have carried out a systematic study on the performance of the photoconductors made from GaN grown by metalorganic chemical vapor deposition using different growth conditions and have found that both response time and responsivity of the GaN detector are improved when the material is grown using increased ammonia flow rates. The best GaN ultraviolet photoconductive detector shows a response time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The characteristics of current photoconductor devices include AlGa1N detectors over the entire range and demonstration of gain mechanism in a metal-semiconductor-metal detector by using interdigitated contact design with a gain over 3000 A/W. 33 Most of the research on UV photodetectors has recently been directed toward the demonstration of AlGa1N basedp-n and p-i-n junction photodiodes, which present the capability of tailoring the cut-off wavelength by controlling the alloy composition and thus the bandgap energy of the active layer. A full range of AlGa1 N p-i-n photodiodes has been demonstrated with a cut-offwavelength continuously tunable from 227 to 365 urn, corresponding to an Al concentration in the range O7O %38394O41 This can be seen in Figure 2 where the current responsivity of these detectors at room temperature is shown.…”
Section: Doping Of Ill-nitridesmentioning
confidence: 99%
“…The characteristics of current photoconductor devices include AlGa1N detectors over the entire range and demonstration of gain mechanism in a metal-semiconductor-metal detector by using interdigitated contact design with a gain over 3000 A/W. 33 Most of the research on UV photodetectors has recently been directed toward the demonstration of AlGa1N basedp-n and p-i-n junction photodiodes, which present the capability of tailoring the cut-off wavelength by controlling the alloy composition and thus the bandgap energy of the active layer. A full range of AlGa1 N p-i-n photodiodes has been demonstrated with a cut-offwavelength continuously tunable from 227 to 365 urn, corresponding to an Al concentration in the range O7O %38394O41 This can be seen in Figure 2 where the current responsivity of these detectors at room temperature is shown.…”
Section: Doping Of Ill-nitridesmentioning
confidence: 99%
“…Such materials and their ternary and quaternary alloy cover the deep-to mid-UV range for devices, such as light-emitting diodes (LEDs), laser diodes (LDs), and UV detectors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] At present, UV detectors are one of the most attractive devices and several research groups have reported photoconductive, 11,12) nitridebased pin-type, 10,13) and Schottky-based metal-semiconductor-metal (MSM) photodetectors. 14,15) However, GaN-based UV detectors needed an external amplifier or a field effect transistor (FET) structure to amplify weak signals, to reduce leak current, and to enhance a low signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the characterization of photoconductive [3][4][5][6], photovoltaic positiveintrinsic-negative (p-i-n) [7] nitride-based photodetectors and Schottky-based metal-semiconductormetal (MSM) photodetectors [8,9]. In contrast, just a very few papers have been published on the characterization of UV detectors working at temperature as high as 700 K. In this work we have studied the role of excitons in two different low barrier metal-semiconductor-metal (MSM) GaN-based UV photodetectors in the temperature range between 300 K and 700 K, by analyzing the temporal response of the devices to short pulses on the millisecond time scale.…”
Section: Introductionmentioning
confidence: 99%